Transmission of SARS‐CoV‐2 Delta variant (B.1.617.2) from a fully vaccinated human to a canine in Georgia, July 2021. (14th April 2022) - Wendling, Natalie M.; Carpenter, Ann; Liew, Amanda; Ghai, Ria R.; Gallardo‐Romero, Nadia; Stoddard, Robyn A.; Tao, Ying; Zhang, Jing; Retchless, Adam C.; Ahmad, Ausaf; Bunkley, Paige; Godino, Claire; et al.
Abstract: SARS‐CoV‐2 infection has been described in a wide range of species, including domestic animals such as dogs and cats. Illness in dogs is usually self‐limiting, and further diagnostics may not be pursued if clinical signs resolve or they respond to empirical treatment. As new variants emerge, the clinical presentation and role in transmission may vary in animals. This report highlights different clinical presentations and immunological responses in two SARS‐CoV‐2 Delta‐variant‐positive dogs with similar exposure to the same fully vaccinated human with a SARS‐CoV‐2 infection and emphasizes the need for active surveillance and additional One Health research on SARS‐CoV‐2 variant infections in companion animals and other species.